Auditory EEG Biomarkers in Fragile X Syndrome: Clinical Relevance - Ethridge, Lauren E.; De Stefano, Lisa A.; Schmitt, Lauren M.; Woodruff, Nicholas E.; Brown, Kara L.; Tran, Morgan; Wang, Jun; Pedapati, Ernest V.; Erickson, Craig A.; Sweeney, John A. (Frontiers in Integrative Neuroscience, 2019)
Sensory hypersensitivities are common and distressing features of Fragile X Syndrome (FXS). While there are many drug interventions that reduce behavioral deficits in Fmr1 mice and efforts to translate these preclinical breakthroughs into clinical trials for FXS, evidence-based clinical interventions are almost non-existent potentially due to lack of valid neural biomarkers. Local circuit function in sensory networks is dependent on the dynamic balance of activity in inhibitory/excitatory synapses. Studies are needed to examine the association of electrophysiological alterations in neural systems with sensory and other clinical features of FXS to establish their clinical relevance. Adolescents and adults with FXS (n=38, Mean age=25.5, std=10.1; 13 females) and age matched typically developing controls (n=40, Mean age=27.7, std=12.1; 17 females) completed auditory chirp and auditory habituation tasks while undergoing dense-array electroencephalography (EEG). Amplitude, latency, and percent change (habituation) in N1 and P2 event-related potentials (ERP) components were characterized for the habituation task; time-frequency calculations using Morlet wavelets characterized phase-locking and single-trial power for both tasks. FXS patients showed increased amplitude but some evidence for reduced habituation of the N1 ERP, and reduced phase-locking in the gamma frequency-range and increased low gamma power to the chirp stimulus. FXS showed increased theta power in both tasks. While the habituation finding was weaker than previously found, the remaining findings replicate our previous work in a new sample of patients with FXS. Females showed less deficit in the chirp task but not the habituation task. Abnormal increases in gamma power were related to more severe behavioral and psychiatric features as well as reductions in neurocognitive abilities. Replicating electrophysiological deficits in a new group of patients using different EEG equipment at a new data collection site with differing levels of environmental noise that were robust to data processing techniques utilizing multiple researchers, indicates a potential for scalability to multi-site clinical trials. Given the robust replicability, relevance to clinical measures, and preclinical evidence for sensitivity of these EEG measures to pharmacological intervention, the observed abnormalities may provide novel translational markers of target engagement and potentially outcome measures in large-scale studies evaluating new treatments targeting neural hyperexcitability in FXS.